Microscopic pore-fracture combination types and their impact on exploration and development: in case of deep shale gas reservoirs in the Luzhou area of the Sichuan Basin - Hu, Zhiming; Duan, Xianggang; Fu, Yonghong; Chang, Yan; Chang, Jin; Jiang, Yuqiang; Yu, Linyao (Frontiers in Earth Science, 2025)
Micro-pores and micro-fractures constitute the most vital reservoir spaces and seepage pathways for shale gas. Conducting an in-depth study of pore-fracture combination types within shale gas reservoirs is beneficial for understanding shale gas enrichment and exploitation. In this study, we conducted a joint experiment involving MICP and WM impregnation on the main gas-producing layer of Longmaxi formation shale reservoir from five shale gas wells in the Luzhou area. This study achieved the visualization of MICP experiments, enabling a quantitative classification of pore volume and micro-fracture volume within the shale reservoir. A QP-F parameter system for classifying pore-fracture combination types has been established to evaluate pore-fracture connectivity, which are categorized into three types. The strongly connected pore-fracture type (SCPFT) shale gas reservoir in the study area has the characteristics of high porosity, high gas content and strong pore-fracture connectivity, which is the preferred target for shale gas exploration and development. Moderately connected pore-fracture type (MCPFT) and weakly connected pore-fracture type (WCPFT) shale gas reservoirs exhibit significant variations in porosity and gas content, coupled with weak pore-fracture connectivity. Despite some of these reservoirs possessing high porosity and gas content, they fail to achieve high production rates. Therefore, during the development of these two types of shale gas reservoirs, it is imperative to enhance and optimize fracturing techniques to create a more intricate fracture network structure, thereby enabling the release of shale gas trapped in poorly connected pores. This research holds significant theoretical and practical implications for identifying optimal shale gas development zones and improving gas recovery efficiency.